Groundhog Day - Ramis, Harold; Albert, Trevor; Rubin, Danny; Murray, Bill, 1950 Sept. 21-; MacDowell, Andie; Elliott, Chris, 1960-; Tobolowsky, Stephen, 1951-; Doyle-Murray, Brian; Fenton, George; Herring, Pembrooke J.; Bailey, John, 1942 Aug. 10-; Erickson, C. O.; et al. (Culver City, Calif. : Columbia TriStar Home Video, 2002)
A romantic comedy about a weatherman caught in a personal time warp where it is Groundhog Day again, and again, and again. First he uses this to his advantage, but then he realizes that he might be doomed to spend the rest of eternity in the same place, seeing the same people, and doing the same thing every day.
DVD, widescreen presentation; Dolby Digital.
English, French, Spanish and Portuguese language soundtracks with optional subtitles in English, French, Spanish, Portuguese, Chinese, Korean and Thai ; closed-captioned in English for the hearing impaired.
Bill Murray, Andie MacDowell, Chris Elliott, Stephen Tobolowsky, Brian Doyle-Murray.
Story, Danny Rubin ; music, George Fenton ; editor, Pembrooke J. Herring ; director of photography, John Bailey ; executive producer, C.O. Erickson.
Originally released as a motion picture in 1993.
MPAA rating: PG.
Keywords: Groundhog Day -- Drama; Television weathercasters -- Drama; Man-woman relationships -- Drama; Dâias festivos -- Teatro; Relaciones hombre-mujer -- Teatro; Feature films; Romantic comedy films; Video recordings for the hearing impaired